2010
DOI: 10.1093/heapol/czq009
|View full text |Cite
|
Sign up to set email alerts
|

Direct facility funding as a response to user fee reduction: implementation and perceived impact among Kenyan health centres and dispensaries

Abstract: There is increasing pressure for reduction of user fees, but this can have adverse effects by decreasing facility-level funds. To address this, direct facility funding (DFF) was piloted in Coast Province, Kenya, with health facility committees (HFCs) responsible for managing the funds. We evaluated the implementation and perceived impact 2.5 years after DFF introduction.Quantitative data collection at 30 public health centres and dispensaries included a structured interview with the in-charge, record reviews a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 9 publications
5
67
0
Order By: Relevance
“…These dimensions of HFMC functioning were chosen based on guidelines (Table 1), findings of the Coast pilot of direct facility funding [6], and characteristics of HFMCs that could be measured quantitatively in a nationally representative survey. Questions were structured using three main approaches, with specific questions and options refined through careful piloting in two districts a .…”
Section: Methodsmentioning
confidence: 99%
“…These dimensions of HFMC functioning were chosen based on guidelines (Table 1), findings of the Coast pilot of direct facility funding [6], and characteristics of HFMCs that could be measured quantitatively in a nationally representative survey. Questions were structured using three main approaches, with specific questions and options refined through careful piloting in two districts a .…”
Section: Methodsmentioning
confidence: 99%
“…Details of the implementation and effects of DFF in general are described elsewhere [16]. This paper assesses the nature and depth of managerial engagement of HFCs at the facility level, and how this has contributed to community accountability in the context of the DFF financing mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the HFCs are involved in a provider payment system for free healthcare in Burkina Faso and Kenya [28,29]. As purchasing is an important strategic lever in UHC, the HFCs could facilitate the registration of eligible users with their primary providers, endorse claims forms and participate in managing facility FMCHP accounts.…”
Section: Discussionmentioning
confidence: 99%
“…As purchasing is an important strategic lever in UHC, the HFCs could facilitate the registration of eligible users with their primary providers, endorse claims forms and participate in managing facility FMCHP accounts. These roles of the HFCs in service provision and provider payment not only needed to be explicitly written in the FMCHP policy, but also required, as Anwari et al [52] observed, consistent implementation through stakeholder engagement, consensus orientation and information sharing with providers and communities, and training to avoid experiences in Kenya where the HFCs were inadequately trained to manage direct facility funding [29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation